On the age-old circle diameter: Solzhenitsyn vs Gorky - Golubkov, Mikhail M. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to the comparison of the creative experience of two great writers of the XX century: Gorky and Solzhenitsyn. Despite the opposite political and philosophical views of the two writers, similar features unite them: the scale of the creative heritage, the presence of epic, dramatic and lyrical works, realism, general aspects of the problems bought looked over. Despite their fundamentally different literary reputations, they are united by the fact that their true appearance is obscured by numerous myths. The article compares the civil positions of writers, analyses their relationship with political power. Much attention is paid to the problems of their creativity, analysis of the types of national life they created, belonging to one historical period: the life of the late XIX – early XX century. However, both writers pay the greatest attention to the interpretation revolution as a way to transform a social life. The article deals with an unusual point of convergence between the two artists: interpretation of images provocateurs as an inevitable evil costs revolutionary work. For Gorky provocateur and provocation is illogical and unexplained from the point of view of real revolutionary. For Solzhenitsyn is natural and logical. Thus, Solzhenitsyn refutes Gorky’s social illusions. The article shows the fundamental difference of philosophical views of the two artists. Gorky is a staunch revolutionary; Solzhenitsyn treats revolution as a criminal attempt on the organic bases of life.